PENGEMBANGAN E-MODUL INTERAKTIF MATERI NEGOSIASI BISNIS MATA PELAJARAN KOMUNIKASI BISNIS KELAS X BDP SMK NEGERI 1 BOJONEGORO - tia ayu hidayah; Harti Harti (FKIP Unswagati, 2021)
AbstractImplementing the independent learning policy during the online learning process can be supported by using learning medias to facilitate students' autonomous learning, one of them is the Interactive E-Module. The purpose of this development research are to 1) analyze the development of an interactive E-Module business negotiation material, 2) the feasibility of developing an interactive E-Module for business negotiation materials, and 3) the response of students to an interactive E-Module for business negotiation materials. This development research uses the 4D R & D model, which consists of 4 stages: defining, designing, developing, and disseminating. However, this study was conducted to develop the stage without performing the deployment phase (disseminate) because of the time, cost, and effort of researchers. Data collection techniques used review sheets and validation of material experts, media experts, and students' responses to limited trials of 10 students anda fiels trials to all students of class X BDP SMKN 1 Bojonegoro. The percentage of validation from material experts was 83.88%, media experts 90%, and the response of students in limited trials was 94.76%, and field trials were 96.76%. Thus it can be concluded that the Interactive E-Module with the criteria is very feasible if it is applied in learning Business Negotiation Material for Class X BDP BDP SMKN 1 Bojonegoro.Key words: Learning Media, Interactive E-Module, Business Negotiation, Business Communication